Reproductive and fetal toxicity studies of histamine H3 receptor antagonist DL76 used in mice to prevent maximal electroshock-induced seizure - Bastaki, Salim M.; Abdulrazzaq, Yousef M.; Zidan, Marwan Abdelrahim; Shafiullah, Mohamed; Alaryani, Saif Ghdayer; Alnuaimi, Fatima Awad; Adeghate, Ernest; Mohsin, Sahar; Akour, Amal; Siwek, Agata; Łażewska, Dorota; Kieć-Kononowicz, Katarzyna; et al. (Frontiers in Pharmacology, 2024)
Introduction: Brain histamine is considered an endogenous anticonvulsant and histamine H1 receptor. H1R antagonists have, in earlier studies, been found to induce convulsions. Moreover, research during the last two decades has provided more information concerning the anticonvulsant activities of histamine H3R (H3R) antagonists investigated in a variety of animal epilepsy models. Methods: Therefore, the in vivo anticonvulsant effect of the H3R antagonist DL76, with proven high in vitro affinity, in vitro selectivity profile, and high in vivo antagonist potency in mice against maximal electroshock (MES)-induced seizures in mice, was assessed. Valproic acid (VPA) was used as a reference antiepileptic drug (AED). In addition, DL76 was tested for its reproductive and fetal toxicity in the same animal species. Results and discussion: Our observations showed that acute systemic administration (intraperitoneal; i.p.) of DL76 (7.5 mg/kg, 15 mg/kg, 30 mg/kg, and 60 mg/kg, i.p.) provided significant and dose-dependent protection against MES-induced seizures in female and male mice. Moreover, the DL76-provided protective effects were comparable to those offered by the VPA and were reversed when animals were co-administered the CNS-penetrant selective H3R agonist R-(α)-methylhistamine (RAM, 10 mg/kg, i.p.). Furthermore, the administration of single (7.5 mg/kg, 15 mg/kg, 30 mg/kg, or 60 mg/kg, i.p.) or multiple doses (3 × 15 mg/kg, i.p.) of H3R antagonist DL76 on gestation days (GD) 8 or 13 failed to affect the maternal body weight of mice when compared with the control mice group. No significant alterations were detected in the average number of implantations and resorptions between the control and DL76-treated groups at the early stages of gestation and the organogenesis period. In addition, no significant differences in the occurrence of skeletal abnormalities, urogenital abnormalities, exencephaly, exomphalos, facial clefts, and caudal malformations were observed. The only significant abnormalities witnessed in the treated groups of mice were in the length of long bones and body length. In conclusion, the novel H3R antagonist DL76 protected test animals against MES-induced seizures and had a low incidence of reproductive and fetal malformation with decreased long bone lengths in vivo, signifying the potential therapeutic value of H3R antagonist DL76 for future preclinical as well as clinical development for use in the management of epilepsy.